Examining the effectiveness of measuring team brand association networks with textual analysis software. (20th December 2019) - Walsh, Patrick; Clavio, Galen
As brand associations are a key component of team brand equity, and ultimately influence consumer behaviour, it is important to have accurate measures of these associations. Previous research has developed scales to measure team brand associations, yet it has been suggested that pre-existing scales may not capture salient features of brands and any unique brand associations not captured by scaled measures. In addition, scales will not uncover the brand association networks and how team brand associations are interconnected. However, with advances in technology there is potential to develop methods which accomplish these goals. This study utilises a freethought listing technique to capture team brand associations which were then analysed by the Leximancer textual analysis software. The results suggest that this method provides an avenue to more accurately uncover the most salient team brand associations and to visualise team brand association networks.